Does the Prevalence of Postpartum Depression Decrease during Quarantine for Covid-19 Pandemic? postpartum depression decrease during quarantine for Covid-19 - Mokhtarian- Gilani, Tahereh; Kariman, Nourossadat (Advances in Nursing & Midwifery, 2021)
Dear Editor, Childbirth can cause serious psychological damage to women. A major complication with a prevalence of 6%-58% in women, postpartum depression (PPD), may emerge 1-18 weeks after delivery [1, 2]. The risk factors of PPD include giving birth in autumn and winter [3], insufficient provision of social and other types of support, financial instability[4], having a history of depression in oneself or one’s relatives, unwanted pregnancy, poor economic status, a high number of children [1], vitamin D deficiency [5] and vitamin c deficiency [6]. A systematic review of 22 studies showed protective effects from healthy dietary patterns, multivitamin supplementation, fish and PUFA intake, calcium, Vitamin D, zinc, and possibly selenium [7]. Honjo et al. found that “who a pregnant woman lives with” affects the risk of PPD in the first month postpartum, and high levels of perceived spouse's involvement in childcare reduced harmful effects/increased protective effect of family members on PPD incidence. These findings suggested that interventions to increase perceived partner's support for childcare may be effective in preventing PPD, regardless of the living situation [8]. A cross-sectional study was conducted from mid-January to late March 2020 by recruiting 262 postpartum women with convenience sampling from clinics affiliated to Shahid Beheshti University of Medical Sciences and some private clinics in Tehran, Iran. The results show reductions in the prevalence of PPD compared to before the outbreak of coronavirus disease 2019 (COVID-19). The Edinburgh Postpartum Depression Scale (EPDS) was used to measure postpartum depression in this study, validated by Montazeri et al. [9]. The investigation started before the COVID 19 pandemic and continued after the pandemic. A significant difference in the postpartum period (P-value < 0.02) was found between EPDS before (10.26 ± 5.79) and after the COVID-19 pandemic (8.70 ± 5.67). PPD decreased from 32% before the COVID-19 pandemic to 26% during the pandemic. The importance of preventing PPD and identifying its relevant factors encouraged the authors to investigate the possible factors affecting the reductions observed in the prevalence of PPD during the COVID-19 pandemic. As a potential determinant of this reduction, the spouse's more extended stay with his wife during the COVID-19 quarantine highlights his supportive role. Furthermore, the lower frequency of commute and newborn visits and fewer parties held to reduce the mother’s fatigue and provide her with more time to spend taking care of her infant. Meanwhile, encouraging the use of vitamin D3 and other supplements, especially vitamin C, by social media to prevent COVID-19 might have increased these substances' use and thereby contributed to preventing PPD. These factors, individually or in combination, could have reduced the prevalence of PPD during the COVID-19 pandemic.